2014
DOI: 10.1016/j.ssc.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Valley- and spin-filter in monolayer MoS2

Abstract: We propose a valley-and spin-filter based on a normal/ferromagnetic/normal molybdenum disulfide (MoS 2 ) junction where the polarizations of the valley and the spin can be inverted by reversing the direction of the exchange field in the ferromagnetic region. By using a modified Dirac Hamiltonian and the scattering formalism, we find that the polarizations can be tuned by applying a gate voltage and changing the exchange field in the structure. We further demonstrate that the presence of a topological term (β) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…In general, the observed behavior proves that the valley-and spin-polarization of the MIGS is highly correlated according to the valley-spin locking in M X 2 materials. Most importantly however, presented results show that the MIGS describe the valley-spin filtering behavior in M X 2 monolayers, in agreement with the predictions made previously within computational modeling studies [21,[29][30][31].…”
Section: Numerical Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In general, the observed behavior proves that the valley-and spin-polarization of the MIGS is highly correlated according to the valley-spin locking in M X 2 materials. Most importantly however, presented results show that the MIGS describe the valley-spin filtering behavior in M X 2 monolayers, in agreement with the predictions made previously within computational modeling studies [21,[29][30][31].…”
Section: Numerical Resultssupporting
confidence: 91%
“…Moreover, the developed theoretical model allows to draw general trends in tuning the filtering properties with respect to the out-of-plane magnetic field strength, the semiconducting channel length, as well as the position of the Fermi level within the energy gap. The obtained filtering characteristics appears to be in agreement with the available computational modeling studies [21,[29][30][31], and should constitute relevant basis for further investigations aimed at the enhancement of valley and spin functionalities in low-dimensional systems. In particular, it is suggested that the best valley and spin selectivity under external magnetic field can be achieved for the Te-based monolayers if the Fermi level is located below the midgap position, according to the large spin splitting effect of the valence band.…”
Section: Discussionsupporting
confidence: 86%
“…Here r = 2 /4m 0 , η = ±1 for valleys K and K , = /2, is the mass term that breaks the inversion symmetry, λ = λ/2, λ is the SOI strength, σ i , i = x,y,z, are the Pauli matrices for the valence and conduction bands, and I is the identity matrix. The parameters α and β depend on the (unequal) electron and hole effective masses and thus pertain to the effective mass asymmetry [34]. Their values for MoS 2 are α = 0.43 and β = 2.21, see Ref.…”
Section: Formalismmentioning
confidence: 99%
“…Due to intrinsic massive Dirac gap (direct band gap of about 1.9 eV ), strong spin-orbit coupling (SOC) caused by dichalcogenide heavy transition metal atom and resulting two nondegenerate K and K ′ valleys relative to spin-up and spin-down quasiparticles at the valence band [35,36,37,38,39] (valley-contrasting spin-splitting 0.1 − 0.5 eV [3]) ML-MDS may exhibit dynamically new behaviors in the Andreev process [40,41] and superconducting Andreev states [42] at the interface of a normal-superconductor.In addition above dynamical peculiar properties of M oS 2 , its layered structure, chemical stability, and relatively high mobility (room temperature mobility over 200 cm 2 /V s) can make it potentially a useful material for electronics applications [5,43,44,45,46]. The spin-valve effect in proximity-induced ferromagnetic M oS 2 may result in a valley-spin-resolved conductance [47,48,49], which is considered as an essential feature for valleytronic devices [39,50,51]. Analogous to graphene, there is a valley index τ = ±1, which is robust against scattering by smooth deformations and long wavelength photons due to a large valley splitting.…”
mentioning
confidence: 99%